Meningkatkan kesadaran dan praktik cuci tangan pada anak usia dini melalui kegiatan penyuluhan dan demonstrasi - Muhammad Sakur; Muhammad Asdar Rustan; Selviani (P3HKI - Universitas Muhammadiyah Parepare, 2024)
Washing hands is a simple but effective action in preventing the spread of infectious diseases, especially in the school environment. This service aims to increase awareness and practice of correct hand washing among young children at Kindergarten Aisyyah 2 Lekkong. The method used is a participatory approach involving interactive counseling, live demonstrations, and the creation of interesting educational media. Counseling is carried out in language that is easy for children to understand, equipped with animated pictures and videos. The demonstration was carried out in stages and actively involved students. Hand-washing guidebooks and attractive posters were also created to strengthen students' understanding. The results of the service implementation showed a significant increase in students' hand-washing knowledge and behavior. Before the activity, students did not consider it important to wash their hands. After the activity, students wash their hands after playing and before eating. In addition, observation results show an increase in the frequency and duration of student hand washing. This change in behavior shows that the service activities have succeeded in building interest and good hand-washing habits in children at Aisyiyah 2 Lekkong Kindergarten.